Identification of Lithium Plating in Lithium-Ion Batteries by Electrical and Optical Methods. Issue 9 (12th May 2020) - Ringbeck, Florian; Rahe, Christiane; Fuchs, Georg; Sauer, Dirk Uwe
Abstract : The detection of lithium plating is a key enabler for the development of fast charging techniques. This work compares different plating detection methods to assess the validity of electrical stripping detection methods. To achieve this, we charged a commercial battery cell under different charging regimes regarding temperature, cooling, current, and maximum voltage. Indicators for plating were collected by electrical stripping measurements as well as optical and laser microscopy measurements on fully charged disassembled cells. The results of the electrical measurements agree with a previous publication by Campbell et al. The disassembled cell shows obvious indications of plating in the form of discolored regions and microscopic indications in the form of dendritic structures on the anodes.